Harmonization of Science: Scientific Paradigm UIN K.H. Abdurrahman Wahid Pekalongan - Seli Septia Ningsih; Tri Bagus Purnama; Regina Wahyu Lintang Kusuma (Yayasan Insan Cendekia Nusantara, 2024)
The scientific philosophy of UIN K.H. Abdurrahman Wahid Pekalongan “Harmonization of Science” is the first step as the basic building block for all institutional activities of UIN K.H. Abdurrahman Wahid Pekalongan which will be developed, both in yhe dharma of education, research and community service. The formulation of the problem in this study is how to harmonize science into a scientific paradigms at UIN K.H. Abdurrahman Wahid Pekalongan? The results of the study show that practices in Islamic educational institutions generally still use the conflict and independence paradigm. Harmonization of science as a solution to human civilization. Design direction for implementing the scientific philosophy of nUIN K.H. Abdurrahman Wahid Pekalongan has five goals in which these goals are developed by departments, study programs, faculties and postgraduates through individual, community and institutional development.